Comment on 'Life cycle environmental impacts of UK shale gas' by L. Stamford and A. Azapagic. Applied Energy, 134, 506–518, 2014. (15th June 2015) - Westaway, Rob; Younger, Paul L.; Cornelius, Chris
Highlights: Commentary on the work cited in the title, published in the journal Applied Energy. This work significantly exaggerates the impacts of shale gas development in the UK. The first cause of exaggeration is underestimation of gas production per well. The second is the assumption that 'dirty' practices that are illegal will be adopted. Accurate information is readily available and should have underpinned this work. Abstract: In the recent work entitled "Life cycle environmental impacts of UK shale gas" (Applied Energy, 134 (2014) 506–518) Stamford and Azapagic (2014) make a first attempt at quantifying a range of overall lifecycle impacts of shale gas production in the UK. Their analysis led to some very unfavourable comparisons with other energy technologies and concluded that, for three types of impact (depletion of the stratospheric ozone layer, photochemical pollution, and terrestrial eco-toxicity), shale gas is 'worse' even than coal as an energy source for generating electricity; furthermore, uncertainties in input data mean that it might also be worse than coal for three additional impacts (on global warming, acidification, and human toxicity). One of their principal inferences is, therefore, that shale gas development in the UK should be subject to stringent environmental regulation, to ensure that it is only developed where it can be demonstrated to regulatory authorities on a well-by-well basis that these and other impacts can be minimized. The present commentary reassesses some of the conclusions reached by this published analysis.